THE IMPLEMENTATION OF DIFFERENTIATED LEARNING IN PAI DAN BUDI PEKERTI SUBJECT AT SMPN 3 GENTENG BANYUWANGI - Muti'atun Muti'atun; Fathi Hidayah (International Conference on Humanity Education and Society (ICHES), 2023)
Differentiated Learning is in accordance with Ki Hajar Dewantara's philosophy that education provides guidance on all natural strengths possessed by children so that children achieve the highest possible safety and happiness both as a human being and as a member of society. Differentiation aims to provide learning rights to students according to their nature. Because every child has different abilities and habits in terms of learning styles. This research was conducted at SMPN 3 Genteng Banyuwangi because at that school the PAI - BP teachers already used Differentiated Learning. and teachers feel the need to do differentiated learning because they see the abilities of each child and the learning style of each child is different. This research was conducted to find out how the implementation of differentiated learning in the subjects PAI-BP. The research used descriptive qualitative method with the main subject is teachers of PAI-BP. Data collection techniques are observation, interviews and documentation. With data validity techniques using triangulation. And the data analysis technique uses three stages, namely data reduction, data presentation and verification/conclusion. The Implementation of Differentiated Learning at SMPN 3 Genteng in two phases: the first phase begins with planning by compiling lesson plans, syllabus, learning materials and media used. In the implementation carried out the identification of student learning styles. The second phase begins with planning, implementing that teacher's grouping students based on student abilities and student learning styles. And the evaluation is done by evaluating knowledge, skills and attitudes.